Plant Nucleolar Stress Response, a New Face in the NAC-Dependent Cellular Stress Responses - Ohbayashi, Iwai; Sugiyama, Munetaka (Frontiers in Plant Science, 2018)
The nucleolus is the most prominent nuclear domain, where the core processes of ribosome biogenesis occur vigorously. All these processes are finely orchestrated by many nucleolar factors to build precisely ribosome particles. In animal cells, perturbations of ribosome biogenesis, mostly accompanied by structural disorders of the nucleolus, cause a kind of cellular stress to induce cell cycle arrest, senescence, or apoptosis, which is called nucleolar stress response. The best-characterized pathway of this stress response involves p53 and MDM2 as key players. p53 is a crucial transcription factor that functions in response to not only nucleolar stress but also other cellular stresses such as DNA damage stress. These cellular stresses release p53 from the inhibition by MDM2, an E3 ubiquitin ligase targeting p53, in various ways, which leads to p53-dependent activation of a set of genes. In plants, genetic impairments of ribosome biogenesis factors or ribosome components have been shown to cause characteristic phenotypes, including a narrow and pointed leaf shape, implying a common signaling pathway connecting ribosomal perturbations and certain aspects of growth and development. Unlike animals, however, plants have neither p53 nor MDM2 family proteins. Then the question arises whether plant cells have a nucleolar stress response pathway. In recent years, it has been reported that several members of the plant-specific transcription factor family NAC play critical roles in the pathways responsive to various cellular stresses. In this mini review, we outline the plant cellular stress response pathways involving NAC transcription factors with reference to the p53-MDM2-dependent pathways of animal cells, and discuss the possible involvement of a plant-unique, NAC-mediated pathway in the nucleolar stress response in plants.